2018
DOI: 10.21009/jobbe.002.1.03
|View full text |Cite
|
Sign up to set email alerts
|

The Effects Of Financial Performance Toward Firm Value With Ownership Structure As Moderating Variable (The Study On Manufacturing Companies Listed In Indonesia Stock Exchange In The Period Of 2012-2016)

Abstract: The aim of this study is to determine the effect of Financial Performance toward Firm Value with Ownership Structure as Moderating Variable on Manufacturing Companies Listed in Indonesia Stock Exchange in The Period of 2012-2016. Independent variable of this study is Financial Performance with Return on Assets as a proxy. Dependent variable of this study is Firm Value with Tobin's Q as a proxy. While moderating variable used in this study is a mechanism of Corporate Governance in the form of Ownership Structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 8 publications
3
16
0
4
Order By: Relevance
“…The higher the company's financial performance, the more it will attract investors to invest so that the company's value increases. The results of this study are in line with research conducted by Chen and Chen (2011); Hatem (2017); Luthfiah and Suherman (2018); Tui, Nurnajamuddin, Sufri, and Nirwana (2017). These studies found that high company financial performance was a good indicator of company progress and able to influence investor decisions that can ultimately increase firm value.…”
Section: Effect Of Financial Performance On Firm Valuesupporting
confidence: 90%
“…The higher the company's financial performance, the more it will attract investors to invest so that the company's value increases. The results of this study are in line with research conducted by Chen and Chen (2011); Hatem (2017); Luthfiah and Suherman (2018); Tui, Nurnajamuddin, Sufri, and Nirwana (2017). These studies found that high company financial performance was a good indicator of company progress and able to influence investor decisions that can ultimately increase firm value.…”
Section: Effect Of Financial Performance On Firm Valuesupporting
confidence: 90%
“…So, it can be said that the higher the company's performance, the higher the firm's value. According to the research of Sudiyatno, Puspitasari, & Kartika (2012), Wibowo (2012) and Luthfiah & Suherman (2018), the results provided understanding to the management. If the company's performance rises, it will cause an increase in company revenue so that company profits will also increase.…”
Section: Effect Of Company Performance On Firm Valuementioning
confidence: 93%
“…According to Luthfiah & Suherman (2018), the firm value will increase in line with the increase in financial performance. Sudiyatno, Puspitasari, & Kartika (2012) stated that company performance is considered a positive signal by market participants as a sign of return on investment.…”
Section: |mentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Sucuahi and Cambarihan (2016), Kabajeh et al (2012) state that financial performance, as measured by the ratio of ROA, ROE, and NPM, has a significant positive effect on firm value. Luthfiah and Suherman (2018) found that the ratio of return on assets had a significant positive effect on Tobin's ratio Q. Alghifari et al (2013) examined the effect of ROA and ROE on firm value as measured by price to book value and Tobin's Q ratio found the result that ROA and ROE significantly positive effect on firm value.…”
Section: Effect Of Financial Performance On Firm Valuementioning
confidence: 99%